Cargo work for maritime operations - House, D. J. (Routledge/Taylor & Francis Group, 2016)
This book covers general principles and the latest international regulations that affect all cargo work, including cargo types, coverage of roll-on/roll-off cargo handling, containerization, equipment and offshore supply. A crucial reference for both students and serving crew. Covers the latest International Maritime Organization (IMO) codes, plus key elements of the International Port and Ship Security Code (ISPS). Includes two new chapters on Passenger Vessels and Offshore Trades.